Beyond Administrative Compliance: Operationalizing the Spirituality Requirement for Notary Appointment under Indonesia's Notary Law - Aziwarti; Machdaliza Masri; Novrida Fauziyah Nasution; Ajasri (HM Publisher, 2024)
The appointment of notaries in Indonesia requires